New mercury(II) halide complexes with neutral ferrocene functionalized thiazolidine‐2‐thiones: Crystallographic and computational analyses. (25th May 2021) - Singh, Ayushi; Singh, Amita; Kociok‐Köhn, Gabriele; Trivedi, Manoj; Kumar, Abhinav
Abstract : Three new Hg(II) complexes with general formula [Hg(L)X2 ]2 (X = Cl (Hg 1 ), Br (Hg 2 ), and I (Hg 3 )) have been synthesized using the novel ferrocenyl functionalized ligand 3‐ferrocenyl methyl‐thiazolidine‐2‐thione (L). The ligand (L) and the complexes have been characterized by Fourier transform infrared (FTIR), multinuclear nuclear magnetic resonance (NMR), electronic absorption, photoluminescence spectroscopies, and single crystal X‐ray diffraction. The single crystal X‐ray diffraction studies indicated that Hg 1 and Hg 2 are centrosymmetric dimers with distorted tetrahedral geometry around the Hg(II) centers generated by the two bridging halides, a terminal halide, and an exocyclic sulfur of ligand. Hg 3 possess two monomers with trigonal planar geometries around Hg(II), which are further held by weak Hg⋯I interactions. Variation in geometrical parameters have been attributed to differences in the nature of the halide donors attached to the Hg(II). The cyclic voltammetry experiments for all the compounds suggested their quasi‐reversible redox properties. Also, the photoluminescent investigation for Hg 1 and Hg 2 indicated medium strong photoluminescence emission at ~500 nm arising due to metal‐to‐ligand charge‐transfer (MLCT) transitions of the ferrocenyl moiety. The solid‐state structure of complexes are stabilized by varied interactions, namely, C–H⋯C and bifurcated H⋯Cl⋯H interactions in Hg 1, C–H⋯C, C–H⋯S, S⋯C (Cp), and C–H⋯Br interactions in Hg 2 and C–H⋯C, C–H⋯S, and C⋯S interactions in Hg 3 . The nature and percentage contribution of all these interactions have been studied by the Hirshfeld surface analyses. The interaction energies for the dimers of all four compounds have been assessed with the help of density functional theory (DFT) and quantum theory of atoms in molecules (QTAIM). Abstract : Three new ferrocene functionalized thiazolidine‐2‐thione HgX2 (X = Cl, Br, and I) complexes synthesized and their crystallographic, electrochemical studies performed and nature of weak interactions in all the compounds addressed using different computational techniques.